Upaya TBM Kuncup Mekar Dalam Membangun Budaya Literasi Masyarakat Pesisir dan Pedesaan di Gunung Kidul, Yogyakarta - Arina Faila Saufa (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2022)
Building a society that is literate to information in rural coastal areas is a challenge for information activists. The lack of access to information such as reading materials and low awareness of the importance of knowledge are often obstacles. This study examines the efforts of the Kuncup Mekar Community Reading Park (TBM) in the village of Kepek Gunungkidul Yogyakarta in building information literacy for people living in coastal and rural areas through the One Home One Library program, so that it has an impact on improving the quality of education and the economy. The author uses qualitative methods with data collection techniques through interviews, observation and documentation. Informants were selected through a purposive technique, namely people who are considered very instrumental and understand the One Home One Library program. Based on the data obtained, TBM Kuncup Mekar conducted the One Home One Library program through 5 (five) stages, namely socialization, preparing bookshelves in each house, distributing books, making book control tools, and arranging book lending schedules. The One Home One Library program has been able to instill public information literacy skills which have an impact on the education and economic aspects of the community. The impact of information literacy skills include; increasing children's interest in reading and learning, the emergence of parents' desire to provide access to learning and information for their children, as well as increasing community understanding in agricultural and livestock cultivation.